If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+7=7(x-3)-3x
We move all terms to the left:
5x+7-(7(x-3)-3x)=0
We calculate terms in parentheses: -(7(x-3)-3x), so:We get rid of parentheses
7(x-3)-3x
We add all the numbers together, and all the variables
-3x+7(x-3)
We multiply parentheses
-3x+7x-21
We add all the numbers together, and all the variables
4x-21
Back to the equation:
-(4x-21)
5x-4x+21+7=0
We add all the numbers together, and all the variables
x+28=0
We move all terms containing x to the left, all other terms to the right
x=-28
| -36=3k-6 | | 9x-1+145=180 | | 16−19k=–20k | | 9x-1=145 | | –3x+2=0 | | 80=7v+10 | | 5x+3=-10x+8 | | -(6-n)=-3n+18 | | 7u+20=12u−15 | | 62=2x+1 | | 16v=17v+18 | | 3/8(-6-2y)=4/8(2y-3) | | 18-6(x+3)=12(x-1) | | -3(4-5a)=30-6a | | 13x+21=34 | | 49=6m+7 | | 2(5x-3)-8=10+4x | | 4x+-5=7 | | 24x-2+70=180 | | 2/3(x+12)=22 | | 17+7j=67 | | 8x=720 | | 8x–200=144 | | 6x-2+116=180 | | B)(x+4)(x+2)-10=0 | | -z+9=11 | | –10+4k=10−k+10 | | -4x+7x+9=3(x+9) | | 6×(22+6)=w | | 6x-2=116 | | 4m+10+8m=–10+10m | | -1.2x-4+x=8+x-6 |